2021
DOI: 10.14569/ijacsa.2021.0120512
|View full text |Cite
|
Sign up to set email alerts
|

A Bird’s Eye View of Natural Language Processing and Requirements Engineering

Abstract: Natural Language Processing (NLP) has demonstrated effectiveness in many application domains. NLP can assist software engineering by automating various activities. This paper examines the interaction between software requirements engineering (RE) and NLP. We reviewed the current literature to evaluate how NLP supports RE and to examine research developments. This literature review indicates that NLP is being employed in all the phases of the RE domain. This paper focuses on the phases of elicitation and the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…[44,45,68,71,73,74],), most studies investigate ambiguity within the scope of individual user stories or between a pair of user stories. This is in line with previous literature reviews [59,60] that observed that most of the reviewed studies aim at detecting ambiguity in single sentences rather than in fragments of text covering multiple requirements. As we demonstrated with our example in Section 2, ambiguity at all linguistic levels can depend on the scope considered.…”
Section: Research Gaps and Opportunitiessupporting
confidence: 89%
See 2 more Smart Citations
“…[44,45,68,71,73,74],), most studies investigate ambiguity within the scope of individual user stories or between a pair of user stories. This is in line with previous literature reviews [59,60] that observed that most of the reviewed studies aim at detecting ambiguity in single sentences rather than in fragments of text covering multiple requirements. As we demonstrated with our example in Section 2, ambiguity at all linguistic levels can depend on the scope considered.…”
Section: Research Gaps and Opportunitiessupporting
confidence: 89%
“…Their review indicated that 56.72% of the reviewed studies applied ontologies to reduce ambiguity when specifying requirements. Kocerka et al [59] and Alzayed and Al-Hunaiyyan [60] performed literature reviews on the use of NLP to improve requirements quality and to automatically detect ambiguity present in requirements. An interesting finding is that most of the reviewed studies aim at detecting ambiguity in single sentences rather than in fragments of text covering multiple requirements.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a considerable amount of research has been undertaken with the aim of designing novel improved solutions to address software development (SD) difficulties [1][2][3], it is crucial to develop an understanding of contemporary software development methods and which of them offers optimal outcomes. Past research has demonstrated that accuracy and completeness in the requirements engineering (RE) practices of developers play a significant part in the success or failure [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…This column represents the percentage of 'yes' answers to questions for failed projects 2. This column represents the percentage of 'yes' answers to questions for successful projects 3.…”
mentioning
confidence: 99%